Factors associated with healthcare satisfaction among patients admitted to a national hospital in Lima, 2018 - Rodríguez Gambetta, Pierina Giovanna (2022)
Objective: To identify the factors associated with healthcare satisfaction among patients admitted to Hospital Nacional Arzobispo Loayza (HNAL) in August 2018. Materials and methods: A survey-based cross-sectional study conducted with 149 patients admitted to the HNAL Internal Medicine ward and selected by simple random sampling. The study included patients ≥18 years and excluded those disoriented to time, place and person, or who did not speak Spanish. An instrument based on a Ministry of Health (MINSA) survey was designed and then validated by experts (coefficient of concordance: 0.9) and a pilot test (Cronbach's alpha: 0.8). Data was processed using Excel and analyzed using SPSS Statistics V12. The variables’ descriptive analysis and association were performed by chi-square test, Fisher's exact test and logistic regression analysis. Results: The main factors were female sex (50.30 %) and primary education (35.57 %). Healthcare satisfaction accounted for 84.60 %. The bivariate analysis showed that satisfaction was associated with education level, customer service, trust, complete physical exam, information on health problems, easy-to-understand information, operation hours, waiting time, comfort, cleanliness, privacy, healthcare personnel (doctors, nurses, technicians) problem-solving skills, and solutions to health problems (p < 0.005). The logistic regression analysis showed that satisfaction was associated with customer service (p = 0.011; CI: 0.03 – 0.462), complete physical exam (p = 0.04; CI: 0.042 – 0.932) and education level (p = 0.06; CI: 0.264 – 0.804).Conclusions: The factors associated with healthcare s atisfaction among patients admitted to HNAL were customer service, complete physical exam and education level. The satisfaction level was high.